Receptor for Advanced Glycation End Products and its Inflammatory Ligands are Upregulated in Amyotrophic Lateral Sclerosis - Juranek, Judyta K.; Daffu, Gurdip K.; Wojtkiewicz, Joanna; Lacomis, David; Kofler, Julia; Schmidt, Ann Marie (Frontiers in Cellular Neuroscience, 2015)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disorder of largely unknown pathogenesis. Recent studies suggest that enhanced oxidative stress and neuroinflammation contribute to the progression of the disease. Mounting evidence implicates the receptor for advanced glycation end-products (RAGE) as a significant contributor to the pathogenesis of certain neurodegenerative diseases and chronic conditions. It is hypothesized that detrimental actions of RAGE are triggered upon binding to its ligands, such as AGEs (advanced glycation end products), S100/calgranulin family members, and High Mobility Group Box-1 (HMGB1) proteins. Here, we examined the expression of RAGE and its ligands in human ALS spinal cord. Tissue samples from age-matched human control and ALS spinal cords were tested for the expression of RAGE, carboxymethyllysine (CML) AGE, S100B and HMGB1, and intensity of the immunofluorescent and immunoblotting signals was assessed. We found that the expression of both RAGE and its ligands was significantly increased in the spinal cords of ALS patients versus age-matched control subjects. Our study is the first report describing co-expression of both RAGE and its ligands in human ALS spinal cords. These findings suggest that further probing of RAGE as a mechanism of neurodegeneration in human ALS is rational.